CONTEXTOS ROMANOS REPUBLICANOS EN BURSAU, UN OPPIDUM EN LA HISPANIA CITERIOR - Serrano Arnáez, Begoña; Bonilla Santander, Óscar; Santos Horneros, Ángel (Rei Cretariae Romanae Fautorum Acta, 2022)
The settlement of Bursau is located in the Cerro del Esquilar (Borja, Spain). This site is a Celtiberian oppidum that played an important role in the Romanization of the territory and was affected by the Roman civil war between Pompeius and Sertorius in Hispania. The excavations carried out between the years 1978-1979, the casual findings and the intervention carried out in 2017 and 2018 have brought to light part of the urban planning of this oppidum. The recovered material culture gives us information about the trade routes in which the oppidum was inserted, with the presence of pottery imported from Italy: Campanian ware and amphorae and pottery from other sites of Iberian Peninsula.